2015
DOI: 10.1080/13607863.2015.1011080
|View full text |Cite
|
Sign up to set email alerts
|

The impact of community-based arts and health interventions on cognition in people with dementia: a systematic literature review

Abstract: Resumen. El presente artículo expone el programa "Retales de una vida" del Proyecto AR.S (Arte y Salud Alzhéimer), proyecto que se viene desarrollando desde el 2011 hasta el 2015. Este proyecto utiliza el archivo y el diario digital y analógico como herramientas para dialogar y trabajar los recuerdos aún latentes en personas con Alzhéimer y otras Demencias, a partir del análisis y pensamiento en imágenes. Los talleres han sido implementados en el Centro de Referencia Estatal para personas con Alzheimer y otras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
114
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(123 citation statements)
references
References 41 publications
7
114
0
2
Order By: Relevance
“…In others, the content and delivery of the intervention is insufficiently described (Mental Health Foundation, 2011;de Medeiros and Basting, 2013). Others appear to be opportunist samples in very specific contexts, which are useful for early, exploratory qualitative investigation, and reflection, but have limited generalizability (Young et al, 2015). Consequently, despite the existence of considerable practice innovations, the research examining effectiveness and impact has been limited, reducing the potential for evidence-based practice and service improvement.…”
Section: The Evidence Base For the Arts In Dementia Carementioning
confidence: 99%
See 2 more Smart Citations
“…In others, the content and delivery of the intervention is insufficiently described (Mental Health Foundation, 2011;de Medeiros and Basting, 2013). Others appear to be opportunist samples in very specific contexts, which are useful for early, exploratory qualitative investigation, and reflection, but have limited generalizability (Young et al, 2015). Consequently, despite the existence of considerable practice innovations, the research examining effectiveness and impact has been limited, reducing the potential for evidence-based practice and service improvement.…”
Section: The Evidence Base For the Arts In Dementia Carementioning
confidence: 99%
“…In some instances, research designs are poorly described, lacking detail of data collection, and analysis (Young et al, 2015). In others, the content and delivery of the intervention is insufficiently described (Mental Health Foundation, 2011;de Medeiros and Basting, 2013).…”
Section: The Evidence Base For the Arts In Dementia Carementioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the people showed more interest, sustained attention, pleasure, self esteem, and normalcy during their participation in the art program, with no differences in negative affect or sadness between the two types of activities. A recent review (Young, Camic, & Tischler, 2015) of the impact of community-based art and health interventions concluded that, despite certain methodological limitations, the studies suggest that art-based activities have a positive impact on cognitive processes, particularly on attention, memory stimulation, improvement of communication, and engagement in creative activities. Participation in a program of looking at art in a public gallery followed by a session of art-making can affect cognition, improving episodic memory, mood, and self-confidence and reducing isolation, as assessed by family caregivers (Eekelaar, Camic, & Springham, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review (Young, Camic, & Tischler, 2016) of the impact of communitybased art and health interventions concluded that, despite certain methodological limitations, the studies suggest that art-based activities had a positive impact on cognitive processes, particularly on attention, memory stimulation, and improvement of communication. Participation in a programme of viewing art in a public gallery followed by a session of art-making can affect cognition, improving episodic memory, mood, and self-confidence and reduce isolation, as assessed by family caregivers (Eekelaar, Camic, & Springham, 2012).…”
mentioning
confidence: 99%